Explication of Tacit Knowledge in Higher Education Institutional Research through the Criteria of Professional Practice Action Research Approach: A Focus Group Case Study at an Australian University - Wong, E.S.K. (Informing Science Institute, 2008)
This paper reports on critical and reflective practitioner heuristic inquiries that investigated a focus group case study of doctoral candidates concerning the adoption and use of the Knowledge Management Processes available to them at an Australian University. In addition, this paper also investigated some research processes of current professional and academic practices. Of particular interest was the conversion of the group’s and the individual’s tacit knowledge into explicit knowledge within the organizational domains, personal domains, or both. This paper brings out inner dialogues and open discourse responses in one-on-one interviews within a phenomenological, reflective practitioner methodology, in order to explain the increased interest in this methodology within the nature of Critical Institutional Research. One area of controversy between Critical Institutional Professional Research and the traditional Institutional Professional Research is the role of “reflective practice,” which remains under-developed. This paper explores the importance of reflective practice employing the term “living thesis paradigm” as a means of developing expert research methods. Finally the conclusions aim to help the individual practitioner develop skills of reflective practice and to help organizational members develop communities of inquiry, as well as to contribute to wider understanding of the place of inquiry in the development of professional practice.